Maritime Policy: Marine Toll to Ensure Availability Of Coconut Trunk Supply Chain On Morotai Island - Karjono, Karjono; Kusumawati, Evyana Diah; Rahmadhani, Rahmadhani (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2022)
The development of the trunk industry in Indonesia is currently growing from year to year along with the increasing population, technological advances, industry, and science. The furniture industry in the current era is increasing over time because this industrial sector provides unique and creative interior designs and artistic values that offer comfort to support various activities. With the development of the furniture industry, the demand for wood has also increased, which has led to increasingly fierce competition in the wood industry. Morotai Island Regency is located at the northernmost tip of North Maluku Province, bordering the Pacific Ocean. Its area is 4,301 km2. Accessibility there is complex, and development growth is still minimal. This area includes underdeveloped, remote, outermost, and border areas (3TP). To achieve the welfare of the people in Morotai Island, the Marine Toll Road is a solution offered to reduce the price disparity for coconut trunks from Morotai, which must pass through Tobelo Regency and then be sent to Java.